Геноцид как прецедентный феномен в политическом дискурсе - Минасян, Наринэ (ԱրՊՀ հրատ․)
The given article deals with the problem of genocide as precedent phenomenon in political discourse as well as its main function. The use of the given precedent phenomenon promotes consolidation of the Armenian nation’s unity (with the help of precedent phenomena the author can have a certain impact, influence on the emotional state of the audience). Precedent phenomenon is regarded to be as one of the main means of persuasion in political discourse. Հոդվածում վերլուծվում է ցեղասպանության` իբրև նախադեպային երևույթի կիրառումը քաղաքական խոսույթում, ինչպես նաև նրա հիմնական գործառույթը: Այս ազգային նախադեպային երևույթի կիրառումը նպաստում է հայ ժողովրդի միասնության ամրապնդմանը: Նախադեպային երևույթների միջոցով հեղինակը /հռետորը/ կարող է որոշակի ազդեցություն ունենալ, ներգործել լսարանի ունկնդրի հուզական վիճակի վրա: Նախադեպային երևույթը քաղաքական խոսույթի համոզման միջոցներից է:
Keywords: Геноцид